Exploring The Use of Social Media As An English Learning Platform During Covid 19 Pandemic - Utami, Valisneria ((JELE) Journal Of English Language and Education, 2022)
Social media is one of the platforms that can be utilized in the teaching process during Covid 19 pandemic. Despite the challenge encountered by lectures in adapting virtual learning mode, social media offers several benefits for instance, it provides practicality, interactivity, and engagement. This study aims to explore the use of social media as a learning platform in the English education study program in UIN Fatmawati Sukarno Bengkulu. This study employed questionnaires and interviews in collecting the data. Sixty students participated to answer the questionnaires and ten students were randomly selected to be interviewed. The result of the study revealed that they showed a positive attitude in using social media as a learning platform. They shared that social media enhances their motivation in language learning and helps them in accessing other learning resources. However, several drawbacks were also yielded such as the absence of authentic language interaction and focus on learning English. Thus, despite the convenience offered by social media, having a lecturer in the classroom is still required to maximize the learning process.